Debating Water : Posthuman Watery Relationality as an Alter-Imaginary to Neoliberal Capitalist Individuality in Ali Smith’s Girl Meets Boy - Räisänen, Rosa-Liina (My University, 2021)
In this thesis, I examine Ali Smith’s novel Girl Meets Boy ([2007] 2015). The novel is part of the Myths series, published by Canongate. The Myths series contains retellings of myths written by contemporary authors. Set in Scotland in 2007, Girl Meets Boy is a retelling of the myth of Iphis and Ianthe from Ovid’s Metamorphoses. I am interested in the critique of neoliberal capitalism in the novel, articulated through the material substance of (bottled) water. Following the socially conscious Modernist literary tradition and as part of the relational turn in literature, Girl Meets Boy utilises the contemporary debate surrounding water and its meanings to critique neoliberal capitalist ideology and practices. My approach is influenced by critique of neoliberalism and capitalism, and posthuman feminism. A theoretical framework for posthuman relationality and interconnection is provided by a consideration of Astrida Neimanis’s figuration ‘bodies of water,’ which I utilise to investigate the ethics of posthuman watery relationality in Girl Meets Boy. On the basis of my analysis, I argue that Girl Meets Boy focuses on the debate surrounding water and its meanings in order to critique neoliberal capitalism. Furthermore, I argue that the novel presents an ethics of posthuman watery relationality as an alter-imaginary to neoliberal capitalist individualism.
Keywords: Ali Smith, Girl Meets Boy, water, bottled water, relationality, watery relationality, interconnection, neoliberal capitalism, neoliberalism, capitalism, individualism, posthumanism, posthuman